2010
DOI: 10.1101/gr.101477.109
|View full text |Cite
|
Sign up to set email alerts
|

ATRX interacts with H3.3 in maintaining telomere structural integrity in pluripotent embryonic stem cells

Abstract: ATRX (alpha thalassemia/mental retardation syndrome X-linked) belongs to the SWI2/SNF2 family of chromatin remodeling proteins. Besides the ATPase/helicase domain at its C terminus, it contains a PHD-like zinc finger at the N terminus. Mutations in the ATRX gene are associated with X-linked mental retardation (XLMR) often accompanied by alpha thalassemia (ATRX syndrome). Although ATRX has been postulated to be a transcriptional regulator, its precise roles remain undefined. We demonstrate ATRX localization at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
356
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(381 citation statements)
references
References 41 publications
21
356
1
3
Order By: Relevance
“…ATRX plays an important role in the incorporation of the histone variant H3.3 into telomeric and pericentromeric DNA (Goldberg et al 2010;Wong et al 2010). It does so with its partner protein Daxx, which directly binds H3.3 and acts as a histone chaperone (Drane Goldberg et al 2010); ATRX both directs where this occurs and facilitates the incorporation of H3.3 into chromatin.…”
Section: What Is the Normal Functional Role Of Atrx?mentioning
confidence: 99%
“…ATRX plays an important role in the incorporation of the histone variant H3.3 into telomeric and pericentromeric DNA (Goldberg et al 2010;Wong et al 2010). It does so with its partner protein Daxx, which directly binds H3.3 and acts as a histone chaperone (Drane Goldberg et al 2010); ATRX both directs where this occurs and facilitates the incorporation of H3.3 into chromatin.…”
Section: What Is the Normal Functional Role Of Atrx?mentioning
confidence: 99%
“…13 ATRX and DAXX form a dimer that acts as a histone chaperone to deposit histone variant H3.3 to GC-rich regions of the genome, including the telomeres, and plays important roles in maintaining telomere stability. [14][15][16] It is hypothesized that dysfunction of the dimer leads to telomere instability, increased telomere homologous recombination, and ultimately, alternative lengthening of telomeres. Subsequent studies have reported frequent ATRX loss (but not DAXX loss) in astrocytoma, leiomyosarcoma, dedifferentiated liposarcoma and other tumor types, and the loss of ATRX has been highly correlated with the alternative lengthening of telomeres phenotype.…”
mentioning
confidence: 99%
“…However, H3.3 is not only confined to sites of active transcription but is also enriched at other genomic regions depending on the developmental context. This is illustrated at the time of fertilization with a massive and global accumulation of H3.3 onto sperm DNA (Loppin et al 2005), and in embryonic stem cells with the accumulation of H3.3 at telomeres Wong et al 2010). How these events are controlled and which factors are involved are beginning to be unraveled (for review, see Elsaesser et al 2010).…”
Section: Replication-independent Deposition Of Histone Variants H33mentioning
confidence: 99%